Learning Curves in Open, Laparoscopic, and Robotic Pancreatic Surgery: A Systematic Review and Proposal of a Standardization. Issue 1 (27th March 2022) - Müller, P. C.; Kuemmerli, C.; Cizmic, A.; Sinz, S.; Probst, P.; de Santibanes, M.; Shrikhande, S. V.; Tschuor, C.; Loos, M.; Mehrabi, A.; Z'graggen, K.; Müller-Stich, B. P.; et al.
Abstract : Objective: To depict and analyze learning curves for open, laparoscopic, and robotic pancreatoduodenectomy (PD) and distal pancreatectomy (DP). Background: Formal training is recommended for safe introduction of pancreatic surgery but definitions of learning curves vary and have not been standardized. Methods: A systematic search on PubMed, Web of Science, and CENTRAL databases identified studies on learning curves in pancreatic surgery. Primary outcome was the number needed to reach the learning curve as defined by the included studies. Secondary outcomes included endpoints defining learning curves, methods of analysis (statistical/arbitrary), and classification of learning phases. Results: Out of 1115 articles, 66 studies with 14, 206 patients were included. Thirty-five studies (53%) based the learning curve analysis on statistical calculations. Most often used parameters to define learning curves were operative time (n = 51), blood loss (n = 17), and complications (n = 10). The number of procedures to surpass a first phase of learning curve was 30 (20–50) for open PD, 39 (11–60) for laparoscopic PD, 25 (8–100) for robotic PD ( P = 0.521), 16 (3–17) for laparoscopic DP, and 15 (5–37) for robotic DP ( P = 0.914). In a three-phase model, intraoperative parameters improved earlier (first to second phase: operating time –15%, blood loss –29%) whereas postoperative parameters improved later (second to third phase: complications –46%, postoperative pancreatic fistula –48%). Studies with higher sample sizes showed higher numbers of procedures needed to overcome the learning curve (rho = 0.64, P < 0.001). Conclusions: This study summarizes learning curves for open-, laparoscopic-, and robotic pancreatic surgery with different definitions, analysis methods, and confounding factors. A standardized reporting of learning curves and definition of phases (competency, proficiency, mastery) is desirable and proposed. Abstract : Abstract : Mini Abstract: Learning curves in pancreatic surgery have not been systematically evaluated and standardized. This systematic review summarizes learning curves for open-, laparoscopic-, and robotic pancreatic surgery with different definitions, analysis methods, and confounding factors. A standardized reporting of learning curves and definition of phases (competency, proficiency, mastery) is proposed. Supplemental Digital Content is available in the text.